Spiritual comfort, spiritual support, and spiritual care: A simultaneous concept analysis - Tavares, Ana Patrícia (2022)
ackground:Spirituality is a dimension of life and the human being that should beincluded in holistic healthcare. One major barrier often described by nurses onimplementing spirituality in practice relates to perceiving the concept of spiritualityas subjective and sharing confounding similarities with other concepts. In this sense,the concepts of spiritual comfort, spiritual care, and spiritual support may requiremore distinct theoretical definitions aimed at clear and effective nursing interven-tions within spiritual care.Aim:To provide a definition of spiritual comfort, spiritual support, and spiritualcare.Methods:Simultaneous concept analysis (SCA) of three concepts according to Haaseet al., which is grounded on Rodgers' evolutionary view. The method was based on aliterature review with the search of electronic databases on May 2020. Search andanalysis have been blinded conducted by two reviewers.Results:One hundred thirty‐six studies were included in the SCA. Findings suggestthat spiritual comfort is an immediate state and an outcome. Spiritual support isrelated with an intimate and positive relationship with God. Spiritual care is definedas a complex and interactive process. Both spiritual support and spiritual care aregrounded in a therapeutic context.Conclusion:This SCA allowed the attributes of each concept to be identified andprovides definitions that may facilitate the understanding of these concepts andpromote the implementation of spirituality in nursing practice, but which has also ledto future research on this topic